(untitled) - Halcoussis, Dennis (Australia, 2005)
Covering all of the main topics, including panel data, that are expected in first econometrics course, Understanding Econometrics uses a new, understandable approach that explains theory intuitively in English, not through a series of mathematical derivations. Recognizing that most students will not be doing economics graduate work, but that they may well need to understand econometrics and how to apply it, this new text focuses on the connection between theory and practice. The text uses a simplified notation system and examples that are integrated with the explanations of the material, fostering comprehension so that the instructor can focus more readily on theory and applications.
Keywords: Econometrics